Behçet's disease and activities of daily living. (19th June 2021) - Nagano, Aoi; Takeuchi, Masaki; Horita, Nobuyuki; Teshigawara, Takeshi; Kawagoe, Tatsukata; Mizuki, Yuki; Meguro, Akira; Nakano, Hiroto; Kirino, Yohei; Takase-Minegishi, Kaoru; Yoshimi, Ryusuke; Kurosawa, Michiko; et al.
Abstract: Objectives: No large-scale registration study has comprehensively evaluated the activities of daily living (ADL) in patients with Behçet's disease. Methods: The Japanese government provided us with a dataset of confirmed or suspected Behçet's disease cases derived from ongoing national registration. ADL were categorized and analysed into four categories in patients who satisfied the International Criteria for Behçet's Disease. Results: Data from 2960 patients (men 38.9%, women 61.1%; median age 39 years) were assessed. While 1767 patients (59.7%) had normal ADL, the others had impaired ADL comprising limited but not assisted [ n  = 1058 (35.7%)], partially assisted [ n  = 116 (3.9%)] and fully assisted [ n  = 19 (0.6%)]. Logistic regression analysis showed that chronic ocular lesions [odds ratio (OR) 1.85 (95% CI 1.46, 2.35), P  < 0.001], paralysis [OR 2.51 (95% CI 1.58, 3.97), P  < 0.001], psychosis [OR 3.16 (95% CI 2.02, 4.95), P  < 0.001] and arthritis [OR 1.69 (95% CI 1.44, 1.99), P  < 0.001] led to the risk of impaired ADL. Chronic ocular lesions [OR 3.61 (95% CI 2.27, 5.72), P  < 0.001], paralysis [OR 3.43 (95% CI 1.87, 6.30), P  < 0.001] and psychosis [OR 3.60 (95% CI 2.00, 6.50), P  < 0.001] were related to the requirement of physical assistance (partially or fully assisted), although arthritis [OR 1.39 (95% CI 0.93, 2.06), P  = 0.108] was not a significant factor in this model. Conclusion: Ocular lesions, neurological manifestations and arthritis affected ADL. Patients with ocular lesions or neurological manifestations more frequently required physical assistance.